Studi Literature : Pelaksanaan Rekam Medis Elektronik Pada Rumah Sakit - Dwi Cahyono; Fatika Nur Rokhimah; Tengku Muhammad Ramdani; Erinaldi (Jurnal Riset Multidisiplin Edukasi, 2025)
Electronic Medical Records (EMRs) are a crucial element in advancing healthcare services, driven by technological and legal advancements, offering benefits such as efficiency, data accuracy, and enhanced patient safety. However, EMR implementation faces challenges, including differences in user perceptions and technical obstacles, necessitating effective strategies to optimize their use. This study aims to describe the challenges and benefits of implementing electronic medical records in hospitals. This study is a literature review using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) framework. It was found that the success of EMR implementation in hospitals is influenced by ease of use, benefits, human resource readiness, and infrastructure. However, challenges such as medical staff resistance, budget constraints, accessibility, and data security risks persist. Effective change management and cost management strategies are necessary to ensure system sustainability. The implementation of Electronic Medical Records (EMRs) enhances healthcare service efficiency, information access, and patient safety. However, it faces challenges such as low digital literacy, system limitations, and inadequate medical staff commitment. Effective strategies are required for optimal EMR implementation..